(untitled) (Journal of Naval Architecture and Marine Engineering, 2023)
The present paper is envisioned for exploring the mathematical model for Jeffrey model fluid with nanoparticle in an inclined tube propagated by peristalsis. The governing two-dimensional equations illustrating the fluid flow are first transformed to make dimensionless and then the exact results were obtained. Small, wave number and Reynolds number approximations are used. Expressions for temperature, concentration, velocity, average flux, pressure drop, coefficient of heat and mass transfer are computed. Streamlines are plotted against pertinent parameters. Also computed streamlines plots to illustrate trapping phenomenon and bolus dynamics to characterise peristaltic propulsion.